2023
DOI: 10.21608/sceee.2023.279484
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Sludge Dewatering Process by Using Green and Environmental Wastes

Abstract: Sludge dewatering is challenging due to sludge's highly compressible nature and the presence of colloidal particles. The capital, operating, and transportation expenses of wastewater management can be decreased by decreasing the amount of water content in the sludge. In the present study, the sludge samples were taken from municipal WWTP, with a moisture content of 98% and specific resistance to filtration (SRF) 1.2265E+16 m/kg. The samples were chemically conditioned with moringa Olivera at different dosages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(17 reference statements)
0
0
0
Order By: Relevance
“…To gain more insight into Moringa's capacity to aid sludge dewatering, see Table 3, which compiles the previous research works that have assessed the variations in dewatering properties (such as the SRF and the CST) that occur when using Moringa as a flocculant. In fact, Rabea et al [62] found that the powder of MO seeds decreased the SRF by up to 70%. This result denotes that filterability becomes greater via powder supplementation, hence promoting sludge water removal.…”
Section: Moringamentioning
confidence: 99%
“…To gain more insight into Moringa's capacity to aid sludge dewatering, see Table 3, which compiles the previous research works that have assessed the variations in dewatering properties (such as the SRF and the CST) that occur when using Moringa as a flocculant. In fact, Rabea et al [62] found that the powder of MO seeds decreased the SRF by up to 70%. This result denotes that filterability becomes greater via powder supplementation, hence promoting sludge water removal.…”
Section: Moringamentioning
confidence: 99%